Lessons on Synthetic Bioarchitectures - Ehmoser-Sinner, Eva-Kathrin; Darren Tan, Cherng-Wen (Springer, 2018)
The objective of synthetic bioarchitectures as a field of research cannot be confined yet as it belongs to the converging sciences, still emerging; however, let us foresee one of the most relevant objectives of this field: the communication of life with synthetic matter. What can we learn by talking to nature in the language of molecules? We can interfere with biological pathways in a much more “compatible” format than has ever been possible before. For example, thinking about chemotherapy we might apply the German saying: “den Teufel mit dem Beelzebub austreiben”—which means that chemotherapy is about trading off: lacking specific tumor markers results in the attempt to stop proliferation in general and the result appears as treating “bad with similar bad”: we kill various cells in the course of chemotherapy and eventually we succeed by hitting cancerous cells harder than benign tissue. The side effects are of course enormous and undesired.
Interaction of Living Matter with Synthetic Structural Analogues